Whole life costing for water distribution network management - Skipworth, Peter (Thomas Telford, 2002)
The deterioration of water distribution networks affects the quality of service delivered to customers, as well as increasing costs to the service provider through the decreasing efficiency of the infrastructure. Whole life costing (WLC) aims to achieve the lowest network provisions and operating cost, when all costs are considered to achieve all statutory standards.